Use of antivascular endothelial growth factor for diabetic macular edema - Rushmia Karim (Dove Medical Press, 2010)
Rushmia Karim, Benjamin TangUniversity of Sydney School of Public Health, Concord Repatriation General Hospital, Concord, NSW, AustraliaBackground: Diabetic macular edema (DME) is one of the manifestations of diabetic retinopathy leading to loss of central vision and visual acuity. It manifests itself with swelling around the central part of the retina, the area responsible for sharp vision. Current treatment includes laser therapy and intravitreal steroids with preventative measures including diabetes control. No one treatment has guaranteed control of diabetic macular edema which leads to deteriorating visual acuity, function and quality of life in patients. Vascular endothelial growth factor (VEGF) has been shown to be a critical stimulus in the pathogenesis of macular edema secondary to diabetes.1 Antiangiogenic therapy encompassed treatment with anti-VEGF which inhibits VEGF-driven neovascularization hence macular edema leading to decreased visual acuity.Objective: For this review, we evaluated the effectiveness of intravitreal anti-VEGF in treating DME.Data sources: We identified five trials (n = 525) using electronic databases (Cochrane Central Register of Controlled Trials [Central], Medline®, and Excerpta Medica Database [EMBASE®]) in October 2008, supplemented by hand searching of reference lists, review articles, and conference abstracts.Methods: We included all randomized clinical trials (RCTs) evaluating any form of intravitreal anti-VEGF for treating DME. The main outcome factor was change in best-corrected visual acuity and central macular thickness. One author assessed eligibility, methodological quality, and extracted data. Meta analysis was performed when appropriate.Results: We included three trials of adequate methodological quality in our metaanalysis. Patients treated with anti-VEGF showed improvement in visual acuity of -0.17 (95% confidence interval [CI]: -0.23, -0.10) and central macular thickness -84.69 (95% CI: -117.09, -52.30). Patients treated with combined anti-VEGF and intravitreal triamcinolone showed improvement of visual acuity of -0.19 (95% CI: -0.27, -0.11) and central macular thickness mean change being –111.20 (95% CI: -148.13, -74.28).Conclusions: Anti-VEGF has been associated with an improvement in visual acuity and central macular thickness in the analysis, however trial analysis was of a short duration and further research is needed to determine long-term benefits.Keywords: anti-VEGF, diabetic macular edema, ranizubimab, Avastin®, pegaptanib